When I Say I’m from India, They Ask Me How to Get a Taxi: Imageries of Connectedness and Disconnectedness among Transmigrants in Melbourne, Australia - Slavková, Markéta (Lidé města, 2014)
This article explores the imaginations of life strategies and negotiations of the notion of the self among young transmigrants, predominantly of Indian origin, who migrated to Melbourne, Australia, on an overseas student visa. The goal of this article is to present dense and complex ethnographic observations of a particular set of imageries, based on which these transmigrants perceived their lives within the context of global migration. I provide the reader insight into who these people are, the imageries that led them on their migration journeys, how these imageries developed in the host country, the repercussions their decisions to migrate had in terms of their imaginations of themselves, and finally, how these transmigrants imagine, experience and negotiate notions of social cohesiveness across the borders of two or more different nation-states.